On Emotions, Knowledge and Educational Institutions: An Explorative Essay - Thomas Karlsohn (Linköping University Electronic Press, 2016)
In this essay I formulate some reflections around the theme feelings and education.1 I will outline some essential features of the research and will argue that a historical approach to the subject will contribute by adding nuance to and complementing the often one-sided and misleading discussions that have marked the debate both within and outside of academia. In a subsequent part of the text I will concretise my reasoning by discussing one specific phenomenon from the past. I have chosen the example of love and will discuss the function it serves in higher education. The focus of the discussion will alternate between the Swedish context and international perspectives.